A new species and new records of Malagasy Megalopinus Eichelbaum (Coleoptera, Staphylinidae, Megalopsidiinae), with notes on the sperm pump in rove beetles - Jałoszyński, Paweł (Zootaxa, 2020)
A new Malagasy megalopsidiine rove beetle, Megalopinus puthzi sp. n., is described; the male morphological structures, including the aedeagus, are described for M. lemur Puthz for the first time, and a new record for M. heissi Puthz is given. The distribution and diversity of the sperm pump within Staphylinidae is discussed; the pump is for the first time reported to occur in Megalopsidiinae, Steninae, and Solieriinae; examples in Euaesthetinae and Scydmaeninae are also illustrated.